Nature's investigator : the diary of Robert Brown in Australia, 1801-1805 - Brown, Robert, 1773-1858.; Moore, David T., 1936-2018; Vallance, T. G.; Groves, Eric W. (Canberra : Australian Biological Resources Study, 2001)
Transcripts of Robert Brown's diaries, supplemented with notes from the writings of Flinders and Good; Brown was the naturalist on the 'Investigator' voyage; maps and diary entries for places visited; mentions contact with Aboriginal peoples, including at: Princess Royal Harbour p. 96-99, 104-5 (includes a word list of eleven words); comments on drawings of van Diemen's land Aborigines at a meeting with Baudin at Encounter Bay, p. 179; at Sandy Cape p. 227; Bongare and Flinders interacting with local people 231-233; Nanberry and others attacked at Port Curtis p. 237-239; Keppel Bay p. 244, 258; Nanbury did not understand the language at Shoalwater Bay p. 259-260; the 'Lady Nelson' which was accompanying the 'Investigator' was sent back to Sydney, taking Nanbaree who was homesick); Murray Islands p. 290-3 (includes word list of five words and three men's names); p. 303 Pennefather River; place name for Mill Creek is Gurakarang or Yierakarang (includes word list of five plant names) p. 445-446; five kinds of kangaroo distinguished p. 446; meeting an Aboriginal party at Port Dalrymple p. 469-470; language of Van Dieman's Land collected by Brown at River Derwent (word list of 31 words) p. 482-483; visit from, then conflict with, Aborigines at Williams River (NSW) p. 553-554.
Includes index.
Bibliography: p. 609-622.
Keywords: Brown, Robert, -- 1773-1858 -- Diaries; Brown, Robert, -- 1773-1858 -- Journeys; Investigator (Ship : Captain = Matthew Flinders); Voyages and travels; Botanists; Language - Vocabulary - Place names; Language - Vocabulary - Word lists; Settlement and contacts - Explorers; Australia -- Discovery and exploration; Derwent River (SE Tas SK55-08, SK55-06); Georges River (S Sydney NSW SI56-05); Princess Royal Harbour (SW WA SI50-11); Shoalwater Bay (E Qld SF56-09); Sandy Cape (Fraser Island, SE Qld SG56-03); Keppel Bay (E Qld SF56-13); Williams River (NSW N Coast SI56-02); Pennefather River (Qld NW Cape York SD54-03); Port Dalrymple (NE Tas SK55-04); Mer / Murray Island (Qld TSI SC55-05); Gladstone / Port Curtis (E Qld SF56-13)